Digital Marketing and Cryptographic Security (D-MARCS) Innovation Design for Marine Tourism Growth: East Java Region - Herlina, Amalia; Santoso, Rudi; Jannah, Sutra Wardatul (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2025)
The growth of marine tourism in East Java faces challenges in digital marketing and the security of tourist transactions. Although digital marketing has been widely implemented, tourists' trust in digital payment systems is still a major obstacle. This research develops the Digital Marketing and Cryptographic Security (D-MARCS) model as an innovative solution that integrates digital marketing based on big data and artificial intelligence (AI) with cryptography-based security technologies, such as blockchain and end-to-end encryption. However, there are still few studies that explore the relationship between digital marketing and transaction security in increasing marine tourism visits, so this study fills the gap. This study uses a mixed-methods approach, with a quantitative method through a survey of 300 tourists and a qualitative method through interviews and focus group discussions (FGD) with tourism managers. The results show that the integration of digital marketing and digital transaction security increases tourist attraction and trust in digital payment systems. The implementation of the D-MARCS model in tourist destinations such as Ayang-Ayang Gresik Beach and Situbondo White Sand Beach increased tourist visits by 40% and digital transactions by 55%. However, this research is still limited to destinations in East Java and faces challenges in the technological readiness and digital literacy of tourism actors. Advanced research can expand coverage to other regions as well as explore new technologies such as augmented reality (AR), Internet of Things (IoT), and metaverse tourism to increase the competitiveness of marine tourism in a sustainable manner.